Respuesta :
Answer:
The first five terms of the sequence are 5, 7, 9, 11 and 13.
Step-by-step explanation:
The first five terms of the sequence are:
a₁ = 2 * (2 - 1) + 3 = 2 * 1 + 3 = 2 + 3 = 5
a₂ = 2 * (3 - 1) + 3 = 2 * 2 + 3 = 4 + 3 = 7
a₃ = 2 * (4 - 1) + 3 = 2 * 3 + 3 = 6 + 3 = 9
a₄ = 2 * (5 - 1) + 3 = 2 * 4 + 3 = 8 + 3 = 11
a₅ = 2 * (6 - 1) + 3 = 2 * 5 + 3 = 10 + 3 = 13
The first five terms of the sequence are 5, 7, 9, 11 and 13.
The required first five terms is 5,7,9,11,13 of the sequence defined by the recursive formula, [tex]a_n = 2(a_n-1)+ 3[/tex] with [tex]a_1 = -2[/tex].
Given that,
Recursive formula; [tex]a_n = 2(a_n-1)+ 3[/tex] with [tex]a_1= -2[/tex]
We have to determine,
The first five terms of sequence defined by recursive formula;
According to the question,
Recursive formula; [tex]a_n = 2(a_n-1)+ 3[/tex],
The first term of the sequence,
[tex]a_n = 2(a_n-1)+ 3\\a_1= 2(2-1)+ 3\\a_1 = 5+ 3\\a_1 = 5[/tex]
The second term of the sequence,
[tex]a_2 = 2 \times (3 - 1) + 3\\a_2 = 2 \times 2 + 3 \\a_2= 4 + 3 \\a_n= 7[/tex]
The third term of the sequence,
[tex]a_3 = 2 \times (4 - 1) + 3 \\a_2= 2 \times 3 + 3 \\a_2 = 6 + 3 \\a_2= 9[/tex]
The fourth term of the sequence,
[tex]a_4 = 2 \times (5 - 1) + 3 \\a_4= 2 \times4 + 3 \\a_4= 8 + 3\\a_4 = 11[/tex]
The fifth term of the sequence,
[tex]a_5 = 2 \times (6 - 1) + 3 \\a_5 = 2 \times 5 + 3 \\a_5= 10 + 3 \\a_5= 13[/tex]
Hence, The required first five terms is 5,7,9,11,13 of the sequence defined by the recursive formula, [tex]a_n = 2(a_n-1)+ 3[/tex] with [tex]a_1 = -2[/tex].
To know more about Series click the link given below.
https://brainly.com/question/12344210